2017
DOI: 10.1002/tesj.339
|View full text |Cite
|
Sign up to set email alerts
|

Improving ELLs' Listening Competence Through Written Scaffolds

Abstract: This article reports findings from a quasi‐experimental study conducted to provide evidence of the effectiveness of written scaffolds (keyword captions, full captions, and full transcript) for different proficiency levels. The gap that this article fills is the lack of research on the type of written scaffold that a specific proficiency level can benefit most from using appropriate materials for the relevant level of language proficiency. Hence, a selective rubric with level‐appropriate written scaffolds is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It is in line with who argue that communication skills are as the main skill in real works because it helps students to express their ideas into their interlocutors. Another skill is listening that can help students to perceive what their interlocutors want and ask to be done (Nation, 2006;Abobaker, 2017). Due to this, the ELT teaching materials are designed with adding certain topics to facilitate students to practice speaking in the Hotel accommodation activities.…”
Section: Resultsmentioning
confidence: 99%
“…It is in line with who argue that communication skills are as the main skill in real works because it helps students to express their ideas into their interlocutors. Another skill is listening that can help students to perceive what their interlocutors want and ask to be done (Nation, 2006;Abobaker, 2017). Due to this, the ELT teaching materials are designed with adding certain topics to facilitate students to practice speaking in the Hotel accommodation activities.…”
Section: Resultsmentioning
confidence: 99%
“…Although Carsen and Judah did some during‐listening activity, they did not focus at the decoding level nor did they scaffold authentic listening experiences. Abobaker's (2017) study found that written scaffolds such as keyword captions, full captions, and full transcripts can support during‐listening instruction across language levels, but teachers need more support to identify appropriate forms of written scaffolds for various levels of learners in order to enhance both listening comprehension and skills. Therefore, future studies might consider how to scaffold longer, authentic listening experiences for teachers’ ease of use.…”
Section: Discussionmentioning
confidence: 99%
“…The above studies seem to suggest that any amount of captions is better than non-caption materials for comprehension (Abobaker, 2017;Guillory, 1998;Montero Perez, Peters, Clarebout, & Desmet, 2014) and vocabulary learning (Montero Perez, Peters, Clarebout, & Desmet, 2014), that the type of captions preferred and how these are used depend on listener proficiency (Abobaker, 2017;Montero Perez et al, 2013;Sydorenko, 2010;Teng, 2019;Vanderplank, 2016), and that pronunciation improves, irrespective of the type of captions used (Mahdi, 2017;Mohsen & Mahdi, 2021).…”
Section: Effects Of Caption Types On Language Learningmentioning
confidence: 90%
“…However, because partial captions are limited to key sentences rather than the full text, they may help learners concentrate more on the listening aspect of the material as they reduce the overall amount of reading required. Keyword captions focus on content words that convey the most meaning from the text and have been shown to likely aid learner concentration on aural messages over visual text (Abobaker, 2017;Vanderplank, 2016), although some learners have also found them distracting (Montero Perez, Peters, Clarebout, & Desmet, 2014).…”
Section: Caption Typesmentioning
confidence: 99%